Trans Fats in America: A Review of Their Use, Consumption, Health Implications, and Regulation - Remig, Valentina; Franklin, Barry; Margolis, Simeon; Kostas, Georgia; Nece, Theresa; Street, James C. (My University, 2010)
Trans fatty acids have long been used in food manufacturing due in part to their melting point at room temperature between saturated and unsaturated fats. However, increasing epidemiologic and biochemical evidence suggest that excessive trans fats in the diet are a significant risk factor for cardiovascular events. A 2% absolute increase in energy intake from trans fat has been associated with a 23% increase in cardiovascular risk. Although Denmark has shown it is possible to all but eliminate commercial sources of trans fats from the diet, total elimination is not possible in a balanced diet due to their natural presence in dairy and meat products. Thus, the American Heart Association recommends limiting trans fats to <1% energy, and the American Dietetic Association, the Institute of Medicine, US Dietary Guidelines, and the National Cholesterol Education Project all recommend limiting dietary trans-fat intake from industrial sources as much as possible. The presence of small amounts of trans fat in hydrogenated or partially hydrogenated oils/food products will likely cause many Americans to exceed their recommended maximum. This likelihood is exacerbated by the Food and Drug Administration labeling rules, which allow products containing <0.5 g trans fat per serving to claim 0 g trans fat. Many products with almost 0.5 g trans fat, if consumed over the course of a day, may approximate or exceed the 2 g maximum as recommended by American Heart Association, all while claiming to be trans-fat free. Accordingly, greater transparency in labeling and/or active consumer education is needed to reduce the cardiovascular risks associated with trans fats.
Keywords: Coronory heart disease; Cardiovascular disease; Energy intake; HDL cholesterol; Portion size; Risk factors; Trans fats